Factors associated with suicide in people who use drugs: a scoping review - Joan Devin; Suzi Lyons; Lisa Murphy; Michael O’Sullivan; Ena Lynn (BMC Psychiatry, 2023)
Abstract Background Suicide is a significant contributor to global mortality. People who use drugs (PWUD) are at increased risk of death by suicide relative to the general population, but there is a lack of information on associated candidate factors for suicide in this group. The aim of this study was to provide a comprehensive overview of existing evidence on potential factors for death by suicide in PWUD. Methods A scoping review was conducted according to the Arksey and O’Malley framework. Articles were identified using Medline, CINAHL, PsycINFO, SOCIndex, the Cochrane Database of Systematic Reviews and the Campbell Collaboration Database of Systematic Reviews; supplemented by grey literature, technical reports, and consultation with experts. No limitations were placed on study design. Publications in English from January 2000 to December 2021 were included. Two reviewers independently screened full-text publications for inclusion. Extracted data were collated using tables and accompanying narrative descriptive summaries. The review was reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. Results The initial search identified 12,389 individual publications, of which 53 met the inclusion criteria. The majority (87%) of included publications were primary research, with an uncontrolled, retrospective study design. The most common data sources were drug treatment databases or national death indexes. Eleven potential factors associated with death by suicide among PWUD were identified: sex; mental health conditions; periods of heightened vulnerability; age profile; use of stimulants, cannabis, or new psychoactive substances; specific medical conditions; lack of dual diagnosis service provision; homelessness; incarceration; intravenous drug use; and race or ethnicity. Opioids, followed by cannabis and stimulant drugs were the most prevalent drugs of use in PWUD who died by suicide. A large proportion of evidence was related to opioid use; therefore, more primary research on suicide and explicit risk factors is required. Conclusions The majority of studies exploring factors associated with death by suicide among PWUD involved descriptive epidemiological data, with limited in-depth analyses of explicit risk factors. To prevent suicide in PWUD, it is important to consider potential risk factors and type of drug use, and to tailor policies and practices accordingly.